2017
DOI: 10.1186/s13065-017-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior and in-vitro antimicrobial screening of some thienylazoaryls dyes

Abstract: BackgroundA series of recently reported phenolic azo dyes 7a–e were prepared by coupling the thienyl diazonium sulfate of 3-Amino-4H-benzo[f]thieno[3,4-c](2H)chromen-4-one with selected diversely substituted phenolic and naphtholic derivatives. These compounds were evaluated for their antibacterial and antifungal activities. Furthermore their voltammetric behavior was compared at a glassy carbon electrode.ResultsThe voltammetric behavior of the five recently reported azo dyes has been compared at a glassy carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The inocula of bacteria and yeasts were prepared from overnight cultures as previously described [ 23 ]. Absorbance was read spectrophotometrically at 530 nm and 600 nm for yeasts and bacteria respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The inocula of bacteria and yeasts were prepared from overnight cultures as previously described [ 23 ]. Absorbance was read spectrophotometrically at 530 nm and 600 nm for yeasts and bacteria respectively.…”
Section: Methodsmentioning
confidence: 99%
“…al. [28] reported the antimicrobial activity of a synthesized novel trisazo dye from 3-amino-4H-thieno [3,4-c][1]benzopyran-4one and Bin et. al.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…16,17 In a recent work, our group reported the electrochemical behavior of azo compounds containing hydroxyl group located at the ortho position of the azo group. 18 In the present study, we extend our investigations to diazo dyes possessing different substituents in order to evaluate the influence of the substituent on the progress of the redox reactions. Indeed, another work has shown that the type of substituent on the aromatic ring of some azo compounds has an influence on the oxidation-reduction.…”
Section: Introductionmentioning
confidence: 99%